CD45RA, a specific marker for leukaemia stem cell sub‐populations in acute myeloid leukaemia. (27th January 2016) - Kersten, Bas; Valkering, Matthijs; Wouters, Rolf; van Amerongen, Rosa; Hanekamp, Diana; Kwidama, Zinia; Valk, Peter; Ossenkoppele, Gert; Zeijlemaker, Wendelien; Kaspers, Gertjan; Cloos, Jacqueline; Schuurhuis, Gerrit J.
Abstract: Chemotherapy resistant leukaemic stem cells (LSC) are thought to be responsible for relapses after therapy in acute myeloid leukaemia (AML). Flow cytometry can discriminate CD34 + CD38 − LSC and normal haematopoietic stem cells (HSC) by using aberrant expression of markers and scatter properties. However, not all LSC can be identified using currently available markers, so new markers are needed. CD45RA is expressed on leukaemic cells in the majority of AML patients. We investigated the potency of CD45RA to specifically identify LSC and HSC and improve LSC quantification. Compared to our best other markers (CLL‐1, also termed CLEC12A, CD33 and CD123), CD45RA was the most reliable marker. Patients with high percentages (>90%) of CD45RA on CD34 + CD38 − LSC have 1·69‐fold higher scatter values compared to HSC ( P  < 0·001), indicating a more mature CD34 + CD38 − phenotype. Patients with low (<10%) or intermediate (10–90%) CD45RA expression on LSC showed no significant differences to HSC (1·12‐ and 1·15‐fold higher, P  = 0·31 and P  = 0·44, respectively). CD45RA‐positive LSC tended to represent more favourable cytogenetic/molecular markers. In conclusion, CD45RA contributes to more accurate LSC detection and is recommended for inclusion in stem cell tracking panels. CD45RA may contribute to define new LSC‐specific therapies and to monitor effects of anti‐LSC treatment.